Complementary and alternative medicine for long COVID: a systematic review of randomized controlled trials - Juan Yang; Kia Hui Lim; Kia Teng Lim; Jeffrey T. Woods; Arya B. Mohabbat; Dietlind L. Wahner-Roedler; Ravindra Ganesh; Brent A. Bauer (Therapeutic Advances in Chronic Disease, 2023)
Background: Complementary and alternative medicine (CAM) interventions are growing in popularity as possible treatments for long COVID symptoms. However, comprehensive analysis of current evidence in this setting is still lacking. Objective: This study aims to review existing published studies on the use of CAM interventions for patients experiencing long COVID through a systematic review. Design: Systematic review of randomized controlled trials (RCTs). Methods: A comprehensive electronic literature search was performed in multiple databases and clinical trial registries from September 2019 to January 2023. RCTs evaluating efficacy and safety of CAM for long COVID were included. Methodological quality of each included trial was appraised with the Cochrane ‘risk of bias’ tool. A qualitative analysis was conducted due to heterogeneity of included studies. Results: A total of 14 RCTs with 1195 participants were included in this review. Study findings demonstrated that CAM interventions could benefit patients with long COVID, especially those suffering from neuropsychiatric disorders, olfactory dysfunction, cognitive impairment, fatigue, breathlessness, and mild-to-moderate lung fibrosis. The main interventions reported were self-administered transcutaneous auricular vagus nerve stimulation, neuro-meditation, dietary supplements, olfactory training, aromatherapy, inspiratory muscle training, concurrent training, and an online breathing and well-being program. Conclusion: CAM interventions may be effective, safe, and acceptable to patients with symptoms of long COVID. However, the findings from this systematic review should be interpreted with caution due to various methodological limitations. More rigorous trials focused on CAM for long COVID are warranted in the future.